TATA KELOLA PRODUKSI TERHADAP KINERJA PADA UMKM - Roni Syahroni; Andrian Noviardy (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of production management on the performance of MSMEs by taking a case study of the Pempek Sutra Sri Gunadi MSMEs in Banyuasin. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through in-depth interviews, observations, and documentation, with key informants consisting of business owners and production employees. The results show that the implementation of good production management, including operational efficiency through scheduling, quality control by grinding fresh fish independently and applying a standard ratio of 4:3, as well as daily inventory management, has a significant impact on business performance. These positive impacts are evident in stable sales growth with an average increase of 15% per year, market expansion to other islands (Java and Bali) through vacuum sealer packaging innovation, and high customer retention rates. In conclusion, improving production management directly increases cost efficiency, minimizes product failure, and ensures the sustainability and profitability of MSMEs.